Higher BNP/NT-proBNP levels stratify prognosis in patients with coronary artery disease but without heart failure. (25th November 2020) - Hendricks, S; Dykun, I; Balcer, B; Al-Rashid, F; Luedike, P; Totzeck, M; Rassaf, T; Mahabadi, A.A
Abstract: Background: Natriuretic peptides (BNP/NT-proBNP) are routinely used for the diagnosis of heart failure and predicts outcome in patients with both heart failure with preserved and reduced ejection fraction. In addition, natriuretic peptides are associated with incident cardiovascular disease manifestation in primary prevention cohorts. Whether the assessment of BNP/NT-proBNP is of value in patients with coronary artery disease but without heart failure has not been investigated in detail. We here evaluate the association of BNP/NT-pro BNP with mortality patients with coronary artery disease but without known chronic heart failure. Methods: The present analysis is based on the ECAD registry of patients undergoing conventional coronary angiography at the Department of Cardiology and Vascular Medicine between 2004 and 2019. For this analysis, we excluded all patients with a diagnosis of heart failure or with elevated BNP/NT-proBNP values at baseline (>100pg/nl for BNP, >400pg/nl for NTproBNP). Moreover, patients with missing follow-up information or without BNP/NT-proBNP levels at admission were excluded. As either BNP or NT-proBNP was available for singular patients, we standardized BNP and NT pro BNP levels based on percentile rank in levels from 0 to 99. Cox regression analysis was used to determine the association of BNP/NT-proBNP with morality in unadjusted and risk factor adjusted models with effect sizes depicted per one standard deviation change in BNP/NT-proBNP rank. Results: Overall, 3738 patients (mean age: 62.8±12.6 years, 71% male) were included in our analysis. During a mean follow-up of 2.6±3.5 years, 172 deaths of any cause occurred. Patients without fatal events had significantly lower BNP/NT-prBNP values compared to patients who died (48.4±28.8 vs. 58.4±27.5, p<0.0001). In unadjusted cox regression analysis, BNP/NT-proBNP increase by one standard deviation was associated with a 47% increased risk of morality (HR (95% CI): 1.47 (1.25–1.72), p<0.0001). Upon adjustment for cardiovascular risk factors, the significant link between BNP/NT-proBNP levels and morality remained (HR (95% CI): 1.38 (1.14–1.66). Effect sizes were similar for patients receiving coronary revascularization therapy as part of the coronary angiography (1.32 [1.03–1.70], p=0.03) as well as for patients with purely diagnostic procedures (1.58 [1.28–1.94], p<0.0001). Conclusion: In patients without heart failure undergoing coronary angiography, BNP/NT-proBNP levels stratify mortality risk independently of traditional cardiovascular risk factors. Our results support the routine assessment of natriuretic peptides also in patients without heart failure to identify patients at increased risk. Funding Acknowledgement: Type of funding source: None